Peningkatan Daya Saing Industri Rumah Tangga dan Usaha Mikro Kuliner melalui Rebranding dan Tata Kelola - Setiany, Erna; Briandana, Rizki; Andika, Julpri; Putra, Yananto Mihadi; Ramadhan, Kurnia; Adriansyah, Andi; Feriyanto, Dafit; Rahayu, Muthia; Zamzami, Annisa Hakim; Yuliawati, Elly; Pratiwi, Riri (LPkM Universitas Bakrie, 2025)
Culinary micro businesses and home industries have a strategic role in local economic development, especially in the Tangerang area. However, obstacles such as low brand awareness, less than optimal business management, and minimal understanding of business regulations hinder the competitiveness of this sector. This study aims to examine how product re-branding and improving business governance can increase the competitiveness of culinary micro businesses. Using the Community-Based Research (CBR) methodology, this community engagement initiative involved 10 business owners selected through purposive sampling, utilizing in-depth interviews and field observations. The results showed that the rebranding strategy, including improving packaging, improving product quality, and strengthening marketing messages, succeeded in increasing sales by up to 30%. In addition, training in financial management, marketing, and operational management improved the skills of business actors. Administrative support in managing permits such as NIB, PIRT, and halal certification also provided more trust to consumers. In conclusion, the combination of an effective rebranding strategy and good business governance can increase the competitiveness of this industry.